Epigenetic disruption of adipogenic gene enhancers in dedifferentiated liposarcomas and its therapeutic value - Hattori, Naoko; Takamatsu, Hironori; Iida, Naoko; Asano, Naofumi; Yamashita, Satoshi; Oba, Gina Miku; Kimura, Kozue; Yoshida, Akihiko; Kobayashi, Eisuke; Nakayama, Robert; Matsumoto, Morio; Nakamura, Masaya; et al. (Frontiers in Oncology, 2025)
Liposarcoma (LPS) is the most common soft-tissue sarcoma in adults, and well-differentiated liposarcoma (WDLPS) and dedifferentiated liposarcoma (DDLPS) are the most frequent subtypes. These LPSs are considered to develop due to disturbances in the adipogenic differentiation of mesenchymal stem cells. However, the molecular mechanisms underlying the disturbances remain unclear. Here, we aimed to identify the mechanism and explore its therapeutic advantages focusing upon their epigenetic alterations, known to be important in differentiation. First, we conducted a genome-wide DNA methylation analysis using 15 LPSs (6 WDLPSs and 9 DDLPSs) and 6 normal adipose tissues. Unsupervised hierarchical cluster analysis using DNA methylation profiles at enhancers classified the samples into the three histological types, whereas analysis using promoters did not. Principal component analysis revealed that normal adipose tissues and WDLPSs were grouped closely, whereas DDLPSs were scattered. Genomic regions hypermethylated in DDLPSs were enriched for enhancers, especially super-enhancers (13.5% of hypermethylated regions and 7.0% of the whole genome), which were located in the genes involved in adipogenesis, such as PPARG2 and its target genes (FABP4 and PLIN1). In addition, marked decreases in PPARG2 and FABP4 expression were confirmed in DDLPSs. Then, treatment of PPARG2-expressing DDLPS cell lines with 5-aza-2’-deoxycytidine, a DNA demethylating agent, and rosiglitazone, a PPARγ agonist, was shown to induce differentiation with enhanced expression of FABP4. These findings indicate that aberrant DNA methylation of adipogenic gene enhancers plays a crucial role in the development of DDLPS and can be a therapeutic target.